Tax reforms in search-and-matching models with heterogeneous agents - Wei Jiang (University of Kent, School of Economics, 2014)
Using a Mortensen-Pissarides search-and-matching framework, this paper investigates the importance of search frictions in determining the welfare and distributional effects of tax reforms that re-allocate the tax burden from capital to labour income. Calibrating the model to the UK economy, we find that the tax reforms are Pareto improving but increase inequality in the long run, despite welfare losses for at least one segment of the population in the short run. The results are robust to the variations in the relative bargaining power of workers and different specifications of unemployment benefit. But the welfare gains are higher for all agents if the relative bargaining power of workers is reduced or we assume that unemployment benefit depends on past wages.
Keywords: E21; E24; E62; 330; search frictions; agent heterogeneity; unemployment benefits; tax reforms